Resident macrophages of the lung and liver: The guardians of our tissues - Kulle, Amelia; Thanabalasuriar, Ajitha; Cohen, Taylor S.; Szydlowska, Marta (Frontiers in Immunology, 2022)
Resident macrophages play a unique role in the maintenance of tissue function. As phagocytes, they are an essential first line defender against pathogens and much of the initial characterization of these cells was focused on their interaction with viral and bacterial pathogens. However, these cells are increasingly recognized as contributing to more than just host defense. Through cytokine production, receptor engagement and gap junction communication resident macrophages tune tissue inflammatory tone, influence adaptive immune cell phenotype and regulate tissue structure and function. This review highlights resident macrophages in the liver and lung as they hold unique roles in the maintenance of the interface between the circulatory system and the external environment. As such, we detail the developmental origin of these cells, their contribution to host defense and the array of tools these cells use to regulate tissue homeostasis.